THE EFFICACY OF COVID-19 VACCINE AND THE CHALLENGE IN IMPLEMENTING MASS VACCINATION IN INDONESIA - TUNAS, I. KETUT; SRI LAKSEMI, DEWA AYU AGUS; WIDYADHARMA, I. PUTU EKA; SUNDARI, LUH PUTU RATNA (International Journal of Applied Pharmaceutics, 2021)
Novel coronavirus, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), has caused more than 2,38 million deaths and more than 108 million cases confirmed in one year of the pandemic are massive upheavals in social life and economy in the international world. An effective vaccine is needed to prevent further morbidity and mortality. This research aims to identify the challenge in implementing mass vaccination in Indonesia which is related to the efficacy of the COVID-19 vaccine. We retrieve sources from relevant and published articles in Google Scholar, Pubmed, DOAJ and Science Direct of articles up to January 2021. The keywords used for gathering information were listed below. Vaccine efficacy is defined as the proportional reduction of a disease case in a group of vaccinated participants compared with unvaccinated participants. The study of vaccine efficacy is a cohort study that is an important vaccine trial method in the field. It is conducted randomly on a large scale by using a control-placebo. During the trials, the country which used the vaccine needs to maintain and observe the vaccine epidemiology. A trial roadmap is expected to identify the condition of the area epidemiologically. Vaccine efficacy is essential to be observed before implementing the vaccine in society. However, intensive socialization about the advantage of vaccines is mainly needed to prevent irrelevant information in social media about mass vaccination.